Do bednets including piperonyl butoxide offer additional protection against populations of Anopheles gambiae s.l. that are highly resistant to pyrethroids? An experimental hut evaluation in Burkina Fasov. Issue 4 (11th July 2018) - Toe, K. H.; Müller, P.; Badolo, A.; Traore, A.; Sagnon, N.; Dabiré, R. K.; Ranson, H.
Abstract: Malaria control is dependent on the use of longlasting insecticidal nets (LLINs) containing pyrethroids. A new generation of LLINs containing both pyrethroids and the synergist piperonyl butoxide (PBO) has been developed in response to increasing pyrethroid resistance in African malaria vectors, but questions remain about the performance of these nets in areas where levels of pyrethroid resistance are very high. This study was conducted in two settings in southwest Burkina Faso, Vallée du Kou 5 and Tengrela, where Anopheles gambiae s.l. (Diptera: Culicidae) mortality rates in World Health Organization (WHO) discriminating dose assays were < 14% for permethrin and < 33% for deltamethrin. When mosquitoes were pre‐exposed to PBO in WHO tube assays, mortality rates increased substantially but full susceptibility was not restored. Molecular characterization revealed high levels of kdr alleles and elevated levels of P450s previously implicated in pyrethroid resistance. In cone bioassays and experimental huts, PBO LLINs outperformed the pyrethroid‐only equivalents from the same manufacturers. Blood feeding rates were 1.6–2.2‐fold lower and mortality rates were 1.69–1.78‐fold greater in huts with PBO LLINs vs. non‐PBO LLINs. This study indicates that PBO LLINs provide greater personal and community‐level protection than standard LLINs against highly pyrethroid‐resistant mosquito populations. Abstract : Pyrethroid‐treated nets are widely used to prevent malaria transmission, but resistance to these insecticides is now widespread in African malaria vectors. Nets containing the pyrethroid synergist piperonyl butoxide (PBO) are available, but the relative performance of standard vs. PBO‐impregnated nets has not been assessed in different settings. This study shows that PBO‐treated nets increase mosquito mortality and reduce blood feeding success in an area in which the mosquito population is extremely resistant to pyrethroids.